(474) Educational Programme to be Incorporated in the Next Medium Term Plan - Klaus Bahr (معهد التخطيط القومى, 2026)
ملخص This historical lecture memo, prepared by the Institute of National Planning in Cairo , elucidates the conceptual and methodological differences between long-term and medium-term educational planning. The paper argues that while long-term plans (spanning 10+ years) are essential for outlining broad perspectives and mobilizing public support, they are inherently non-operational for day-to-day administration. Conversely, medium-term plans (3 to 7 years) serve as the critical operational link, translating macroscopic targets into concrete, resource-constrained actions. A central theme is the structural time-lag (gestation period) inherent in education. Unlike physical production, generating highly qualified manpower (HQM) or secondary/university graduates requires 12 to 16 years, primarily due to persistent teacher shortages. Consequently, linear interpolations of long-term targets fail. In the initial phases, planners must work "backwards"—starting from the longest production cycles—and prioritize eliminating structural bottlenecks (like teacher training) rather than pursuing uniform, uncoordinated expansion that compromises system efficiency. Ultimately, the author reframes the educational planner not as a mere technocrat, but as a strategic negotiator who rationalizes resource allocation alongside other economic sectors, reconciling long-term political visions with immediate financial realities. توضح هذه المذكرة المحاضراتية التاريخية، التي أعدها معهد التخطيط القومي بالقاهرة ، الفروق المفاهيمية والمنهجية الجوهرية بين التخطيط التعليمي طويل المدى ومتوسط المدى وتتلخص أطروحة الورقة في أن الخطط طويلة المدى (10 سنوات فأكثر) ، رُغم أهميتها في رسم الرؤى العامة وحشد الدعم الشعبي والسياسي ، هي خطط غير تشغيلية بطبيعتها ولا تصلح لاتخاذ القرارات اليومية. في المقابل، تبرز الخطط متوسطة المدى (من 3 إلى 7 سنوات) كحلقة وصل تشغيلية حاسمة تترجم المستهدفات الكلية إلى إجراءات واقعية تراعي قيود الموارد المتاحة كما تسلط المذكرة الضوء على مشكلة "فترات الإعداد والإنتاج" الطويلة الكامنة في النظام التعليمي ؛ فحاجة الاقتصاد إلى القوى العاملة عالية التأهيل (HQM) أو خريجي الجامعات تتطلب فترات زمنية تتراوح بين 12 إلى 16 سنة ، وتتأثر بوجود اختناقات هيكلية حتمية مثل نقص المعلمين. بناءً على ذلك، يفشل الاعتماد على المتوسطات الحسابية البسيطة للمستهدفات طويلة المدى ، ويتعين على المخطط العمل "عكسياً" بدءاً من المراحل التعليمية ذات دورة الإنتاج الأطول، مع التركيز على الاستثمار الانتقائي في العوامل ذات الأثر المضاعف (مثل تدريب المعلمين) عوضاً عن التوسع العشوائي ختاماً، يعيد الكاتب تعريف المخطط التعليمي؛ فهو ليس مجرد تكنوقراطي جامد ، بل مفاوض استراتيجي يوازن بين الموارد المحدودة والقطاعات الاقتصادية الأخرى، ليضمن تحويل الطموحات السياسية إلى قرارات عقلانية قابلة للتطبيق. . . .